(untitled) (Modern education and development, 2025)
This study explores the integration of reading and writing skills as a means to enhance essay writing proficiency among intermediate English learners. In many educational contexts, reading and writing are often taught as separate skills, despite their interconnected nature. This research aims to demonstrate that using reading texts as models and sources of input can significantly improve learners’ organization, vocabulary use, grammar accuracy, and idea development in writing tasks. The study involved 25 intermediate-level students at an academic lyceum who participated in integrated reading-writing activities over a four-week period. Data was collected through pre- and post-writing tasks, classroom observations, and student feedback. The findings suggest that integrating reading and writing not only increases learner engagement but also supports the development of more structured and coherent essays. The results highlight the importance of designing language lessons that bridge receptive and productive skills for more effective language acquisition.